Plant aquaporins : from transport to signaling - Chaumont, François; Tyerman, Stephen D. (Springer, 2017)
Aquaporins are channel proteins that facilitate the diffusion of water and small uncharged solutes across cellular membranes. Plant aquaporins form a large family of highly divergent proteins that are involved in many different physiological processes. This book will summarize the recent advances regarding plant aquaporins, their phylogeny, structure, substrate specificity, mechanisms of regulation and roles in various important physiological processes related to the control of water flow and small solute distribution at the cell, tissue and plant level in an ever-changing environment.
Keywords: Aquaporins.; Plant physiology.; elektronické knihy; electronic books